Effect of Processed Moringa oleifera and Clarias sp. on Hemoglobin Levels of Pregnant Women - Fatmawati, Nurul; Ariendha, Dian Soekmawaty Riezqy; Zulfiana, Yesvi (Universitas Islam Bandung, 2025)
Anemia has a significant impact on maternal health, growth, and fetal development during pregnancy. These nutritional problems can be prevented by increasing food consumption containing protein and iron. One form of local wisdom used as an alternative is the use of Moringa oleifera leaves and Clarias sp. (catfish). This study aims to determine the effect of giving catfish nuggets mixed with Moringa oleifera leaf flour on hemoglobin levels in pregnant women with anemia. The design used in this study was experimental, with a one-group pre-post test design. This study consisted of a treatment group that received catfish nuggets and Moringa oleifera leaves and continued to take Fe tablets. The treatment group received nuggets for 30 days, once a day in the afternoon, and then the control group was given Fe tablets. The subjects in this study were 32 pregnant women who experienced anemia. This study was conducted from August 21 to September 20, 2024, at the Sesele Public Health Center in Lombok Barat regency. The results of the study showed that the p-value was smaller than the significance level of 5% (0.05), namely 0.000<0.05, catfish nuggets and Moringa oleifera leaves significantly affect the increase in hemoglobin levels in pregnant women. This study concludes that catfish nuggets and Moringa oleifera leaves can increase hemoglobin levels in pregnant women. Therefore, consuming catfish nuggets and Moringa oleifera leaves regularly can cure anemia.